The Impact of Emotional Intelligence on Public Employees’ Job Stress and Willingness to Deliver High-Quality and Performant Public Services - Oana Matilda Sabie; Corina Cristina Nastacă; Maria Roxana Brișcariu (Transylvanian Review of Administrative Sciences, 2025)
Too little has been published on emotional intelligence in the public sector, despite the scientific literature’s increased interest in the concept in recent years. The present research aim is to analyze whether and how public employees’ emotional intelligence (EI) has an influence on their job stress (JS) level and willingness to deliver quality and performant public services (WDQS). In order to investigate the hypotheses, the study used a quantitative methodology and a conceptual deductive research technique based on a conceptual framework. For statistical analysis, we used the SPSS Statistics 22.0 program. This made it possible for us to build descriptive analyses and run several parametric tests to achieve the primary goal of our study. The findings showed that the employees of the National Agency for Public Procurement from Romania (ANAP) registered an average to above average EI level (M = 4.99), with no relevant significant influence on their stress level, and with a weak influence on their willingness to deliver quality public services. The study’s respondents, although they register a high level of job stress (M = 5.44), demonstrated an average desire to deliver qualitative services to different stakeholders (M = 4.89), with low to average impact on the provided public services’ performance (M = 3.19). From all the main sample characteristics, only the occupied position in the organization (independent variable) had a positive significant influence on employees’ EI and JS level. In order to allow for comparisons of the results with those of the current study, future research should combine various methods of measuring emotional intelligence, job stress and public employees’ willingness to provide quality and performant public services.